2013
DOI: 10.1111/evo.12152
|View full text |Cite
|
Sign up to set email alerts
|

STEPWISE EVOLUTION OF RESISTANCE TO TOXIC CARDENOLIDES VIA GENETIC SUBSTITUTIONS IN THE NA+/K+-ATPASE OF MILKWEED BUTTERFLIES (LEPIDOPTERA: DANAINI)

Abstract: Despite the monarch butterfly (Danaus plexippus) being famous for its adaptations to the defensive traits of its milkweed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
119
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 53 publications
(91 reference statements)
3
119
0
Order By: Relevance
“…Na þ /K þ -ATPase assays were performed as described in Petschenka et al [31]. Briefly, brains and thoracic ganglia of hemipteran specimens (killed and stored at 2808C) were dissected under deionized water, pooled (see table 1 for numbers of individuals used) and homogenized in deionized water (500 ml) using an all glass grinder (Wheaton).…”
Section: Kleidocerys Resedae Belonochilus Numeniusmentioning
confidence: 99%
See 1 more Smart Citation
“…Na þ /K þ -ATPase assays were performed as described in Petschenka et al [31]. Briefly, brains and thoracic ganglia of hemipteran specimens (killed and stored at 2808C) were dissected under deionized water, pooled (see table 1 for numbers of individuals used) and homogenized in deionized water (500 ml) using an all glass grinder (Wheaton).…”
Section: Kleidocerys Resedae Belonochilus Numeniusmentioning
confidence: 99%
“…Cardenolide sensitivity of Na þ /K þ -ATPase was determined by photometric quantification of inorganic phosphate released from ATP by Na þ /K þ -ATPase at different concentrations of ouabain over a period of 20 min at 378C. To test for linearity, we measured a time course of P i release over the period of incubation (reactions stopped after 0, 5, 10, 15 and 20 min) using a Na þ /K þ -ATPase preparation of O. fasciatus under all reaction conditions (10 23 to 10 28 M plus controls) and found that P i release was always linear (see [31] and the electronic supplementary material, figure S2). Linearity under all conditions ensures that ouabain inhibition curves are not biased by nonlinear P i release over time under different incubation regimes.…”
Section: Kleidocerys Resedae Belonochilus Numeniusmentioning
confidence: 99%
“…Despite the widespread appreciation of sequestration as an extreme component of host plant specialization and adaptation against predation [9,10], the mechanisms of how sequestration integrates into coevolutionary theory [3,11] are barely understood. To test the relative importance of coping with a toxic diet versus sequestration of toxins in shaping insect adaptations, here we assess the functional consequences of an evolutionarily escalating resistance trait across the milkweed butterflies [12,13]. Cardenolides (cardiac glycosides) are highly potent plant toxins that specifically inhibit Na þ /K þ -ATPase, an essential animal cation transporter [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 16 species of Danaini whose Na þ /K þ -ATPase genes were sequenced and Na þ /K þ -ATPases physiologically assayed, resistance to cardenolides was determined by three discrete molecular forms [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation